Improved repair of rabbit calvarial defects with hydroxyapatite/chitosan/polycaprolactone composite scaffold-engrafted EPCs and BMSCs - Yu, Hedong; Xia, Lingyun; Leng, Xieyuan; Chen, Yongji; Zhang, Li; Ni, Xiaobing; Luo, Jie; Leng, Weidong (Frontiers in Bioengineering and Biotechnology, 2022)
Endothelial progenitor cells (EPCs) expressing vascular endothelial growth factor (VEGF) and platelet-derived growth factor (PDGF), and bone marrow mesenchymal stem cells (BMSCs) expressing endogenous bone morphogenetic protein 2(BMP-2), play the important role in new bone formation. In this study it was investigated the effects of a porous polycaprolactone (PCL) / chitosan (CS) / hydroxyapatite (HA) composite engrafted EPCs and BMSCs on expression of BMP-2, VEGF and PDGF in calvarial defect rabbit model. The results showed that PCL/CS/HA + EPCs, PCL/CS/HA + BMSCs and PCL/CS/HA + EPCs + BMSCs groups had more obvious repair effect in the eighth week compared with PCL/CS/HA group. PCL/CS/HA + EPCs + BMSCs group present especially significant improvement on the percentages of bone volume at week 4 and week 8, with obvious bone growth. Collectively, PCL/CS/HA composite scaffold engrafting EPCs and BMSCs is effective to repair bone defects through regulating endogenous expression of BMP-2, VEGF and PDGF. This study provides important implications for the potential clinical application of composite scaffold of biomaterial engrafted engineering cells.